VISUALIZING SYNTAX: THE EFFECTIVENESS OF TREE DIAGRAM-BASED SENTENCE PARSING IN ADDRESSING STRUCTURAL AMBIGUITY IN EFL - Bochari, Siska; Hastini, Hastini (Universitas Labuhanbatu, 2025)
Purpose – This study explores how syntax tree diagrams can help English as a Foreign Language (EFL) students better understand sentences that can be interpreted in multiple ways due to their structure. Structural ambiguity often confuses EFL learners, who may struggle to see how a sentence could have different meanings. While ambiguity in language is not new, there has not been much focus on practical ways to teach students how to deal with it.Methodology – Employing a pre-experimental one-group pretest-posttest design, this study involved 35 fifth-semester English Study Program students at Tadulako University. Participants received six sessions of instruction using syntax tree-based sentence parsing. Data were collected through a pretest, a post-test, and a structured questionnaire. The data were analysed using descriptive statistics and paired sample t-tests to determine whether the method had a significant impact.Findings – The findings verified that students developed better skills to understand ambiguous sentences. The post-test scores exceeded pretest scores, and students demonstrated improved abilities to recognize how different sentence arrangements produce different meanings. The questionnaire results confirmed that students developed increased confidence through the syntax tree method, which helped them understand sentence structure.Contribution – This research demonstrates that visual tools, such as a syntax tree, provide valuable benefits for teaching English syntax to students. This research demonstrates that showing students sentence structure through visualization helps them understand complex grammar rules better. The findings present practical information for teachers who want to develop better classroom methods for teaching ambiguous sentence structures